Social Competence and Peer Social Acceptance: Evaluating Effects of an Educational Intervention in Adolescents - Luna, Pablo; Guerrero, Jerónimo; Rodrigo-Ruiz, Débora; Losada, Lidia; Cejudo, Javier (Frontiers in Psychology, 2020)
This study aims to evaluate the impact of an educational intervention on social competence and social acceptance among adolescents. The participants were 106 adolescents aged 12-15 years (M = 13.41 years; SD = 0.81 years). Participants were randomly assigned to the control group (n = 44) and an experimental group (n = 69). In the experimental group, an intervention based on the Sport Education Model (SEM) was applied. While in the control group, an intervention based on the Traditional Model of Direct Instruction (TM-DI) was carried out. An experimental design with repeated pretest and posttest measurements was developed. The Adolescent Multidimensional Social Competence Questionnaire (AMSC-Q) was used to assess social competence. The Guess Who (GW4) questionnaire was used to assess social acceptance (SA) among peers. The preliminary results obtained in this investigation showed that the intervention based on the SEM (experimental group) promoted greater improvements in some indicators of social competence and social acceptance among peers than those obtained with the TM-DI (control group). Furthermore, the results confirm a similar impact of the intervention between boys and girls. It is also relevant to note that these findings highlight the efficacy, feasibility, and suitability of this educational intervention with adolescents.